2023
DOI: 10.1136/jnis-2023-020104
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted microcatheter shaping for intracranial aneurysm embolization: evaluation of safety and efficacy in a multicenter randomized controlled trial

Abstract: BackgroundThis study aimed to evaluate the efficacy, stability, and safety of computer-assisted microcatheter shaping (CAMS) in patients with intracranial aneurysms.MethodsA total of 201 patients with intracranial aneurysms receiving endovascular coiling therapy were continuously recruited and randomly assigned to the CAMS and manual microcatheter shaping (MMS) groups. The investigated outcomes included the first-trial success rate, time to position the microcatheter in aneurysms, rate of successful microcathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Ultimately, all 30 microcatheters accurately entered the aneurysmal sac, while 25 achieved satisfactory results in terms of position within the sac and intraoperative stability (illustrated in Figure 4 ) ( 6 ). In a recently published multicenter randomized controlled study on the clinical application of this software ( 49 ), 101 patients underwent treatment with computer-assisted microcatheter shaping technology (CAMS group), while another 100 patients underwent conventional manual microcatheter shaping methods (MMS group). The result indicated that the CAMS group showed significant superiority over the MMS group in terms of the success rate of the first attempt (96.0 vs. 66.0%, P < 0.001), success rate of microcatheter placement within 5 min (96.0 vs. 72.0%, P < 0.001), microcatheter stability (97.0 vs. 84.0%, P = 0.002), and excellent delivery performance without microwire guidance (45.5 vs. 24.0%, P < 0.001).…”
Section: Methods and Search Strategymentioning
confidence: 99%
“…Ultimately, all 30 microcatheters accurately entered the aneurysmal sac, while 25 achieved satisfactory results in terms of position within the sac and intraoperative stability (illustrated in Figure 4 ) ( 6 ). In a recently published multicenter randomized controlled study on the clinical application of this software ( 49 ), 101 patients underwent treatment with computer-assisted microcatheter shaping technology (CAMS group), while another 100 patients underwent conventional manual microcatheter shaping methods (MMS group). The result indicated that the CAMS group showed significant superiority over the MMS group in terms of the success rate of the first attempt (96.0 vs. 66.0%, P < 0.001), success rate of microcatheter placement within 5 min (96.0 vs. 72.0%, P < 0.001), microcatheter stability (97.0 vs. 84.0%, P = 0.002), and excellent delivery performance without microwire guidance (45.5 vs. 24.0%, P < 0.001).…”
Section: Methods and Search Strategymentioning
confidence: 99%